Quality Control Study of Different Products from Famotidine Tablets in the Iraqi Market - Jassem, Nizar (Vitae, 2022)
Background: In developing countries, particularly in Iraq, the use of generic medicines has been increasing in recent years, primarily as a cost-saving measure in healthcare provision. In the Iraqi market, famotidine tablets are available from different pharmaceutical companies. As a result, regular pre-marketing quality testing is required to check the quality and identify which product might safely substitute the innovator product in the event of the innovator brand's unavailability or high cost. Objective: various quality control tests have been conducted to determine the Pharmaceutical Equivalence of the different generic and brands of Famotidine film-coated tablets marketed in Iraq. Materials and Methods: Four different samples of the most commonly available Famotidine 20 mg tablets in the Iraqi market were tested for drug contents, friability, and hardness. Additionally, the in-vitro drug release and kinetics were evaluated. Results: slight differences in the products’ content were found; however, they were within the acceptable requirement of British Pharmacopeia (BP) and The United States Pharmacopoeia (USP) 30, NF 25. Similarly, the friability and hardness were within the excellent range according to the B.P. and USP. The results of our study indicated that the tested brand (Famodin) and the three generic products (Famosam, Ulceran, and Famodar) of Famotidine tablets have a unique pattern of in-vitro release profiles. However, all the tested brands and generic pills complied with the USP specifications for the immediate release dosage forms except for Famosam. Release kinetic for the four tested products indicates first-order kinetic models. Conclusion: The findings revealed that nearly all of the tested Famotidine tablet brands and generics met the pharmacopeial requirements for oral tablets. As a result, if acquiring the innovative brand of famotidine tablets is difficult to obtain, healthcare providers may be advised to use the tested products instead.